Localized attack of copper and brass in tap water: The effect of Pseudomonas - Valcarce, María Beatriz (2005)
The presence of Pseudomonas fluorescens in artificial tap water (ATW) affects the composition of the oxide layer and the susceptibility to pitting corrosion of copper and 70/30 brass. The surface layer was investigated by means of a combination of electrochemical and spectro-electrochemical techniques involving cyclic voltammograms, potentiodynamic reduction curves, anodic polarisation curves, weight-loss tests and reflectance spectroscopy. In the sterile conditions the mass loss is lower in brass than in copper while the presence of bacteria enhances the attack in brass. Dezincification in inoculated electrolyte was revealed by microscopic observation, as well as by potentiodynamic reduction curves. Zn dissolution was also supported by spectroscopic evidence. Slow-rate voltamperometric curves were used to determine potential values characteristic of localized corrosion. In the presence of bacteria, the pitting potential moves towards more positive values for both materials but the difference between the repassivation and the pitting potential increases. Bigger and deeper pits can be seen in the presence of microorganisms. © 2004 Elsevier Ltd. All rights reserved.